2020
DOI: 10.1088/1741-2552/aba55f
|View full text |Cite
|
Sign up to set email alerts
|

Contra-lateral desynchronized alpha oscillations linearly correlate with discrimination performance of tactile acuity

Abstract: Objective. We used EEG to investigate cortical oscillatory activities during the tactile discrimination task and characterize the correlation between the EEG features and subjects’ discrimination performance. Approach. Transcutaneous electrical nerve stimulation (TENS) was applied on two finger areas (thumb and index for healthy hands, thumb and index-projected areas for disabled hands) to evoke two kinds of tactile sensations (vibration and pressure) with three levels of intensities (low, medium and high). Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 54 publications
2
14
1
Order By: Relevance
“…Decreases in alpha (8-12 Hz) and beta (17-25 Hz) oscillatory power indicated activation of the somatosensory system during the tactile stimulus presentation and confirmed the inhibition hypothesis. Previous studies mentioned that suppression of alpha power (ERD) reflects activation processes, while increases in alpha power (ERS) indicate inhibitory control processes [87,88]. However, we also did not observe the modulatory effects of oscillatory activity induced by tACS as no changes in the power of alpha and beta bands occurred after stimulation.…”
Section: Tacs Effects On Evoked and Induced Oscillatory Power Changes...contrasting
confidence: 90%
“…Decreases in alpha (8-12 Hz) and beta (17-25 Hz) oscillatory power indicated activation of the somatosensory system during the tactile stimulus presentation and confirmed the inhibition hypothesis. Previous studies mentioned that suppression of alpha power (ERD) reflects activation processes, while increases in alpha power (ERS) indicate inhibitory control processes [87,88]. However, we also did not observe the modulatory effects of oscillatory activity induced by tACS as no changes in the power of alpha and beta bands occurred after stimulation.…”
Section: Tacs Effects On Evoked and Induced Oscillatory Power Changes...contrasting
confidence: 90%
“…These studies have, mostly, explored EEG correlates of tactile processing using stimulation current, textures, or vibratory stimuli; due to their ability to generate EEG evoked responses. For example, previous studies have found that changes in the alpha frequency band in the C3 electrode are correlated to tactile performance [24]. However, based on our previous study [13], analysis of passive tactile width discrimination in humans may bene t from analysis of longer periods (e.g., larger than 1.0 second) due to the relatively large period of contact occurring between the bars and the nger.…”
Section: Introductionmentioning
confidence: 80%
“…Power changes in theta, alpha, and beta frequency bands for the C3 electrode during discrimination and response periods, as well as the changes in ratios of frequencies, are in line with previous studies of tactile function. Tactile discrimination is often associated with changes in EEG activity recorded from the electrode C3/4, namely with the appearance of event related potentials or power changes in alpha and beta frequency bands [17][18][19][20][21][22][23][24][28][29]. For example, a relevant contribution of mu (8-15 Hz) and beta (16-30 Hz) frequency bands has been demonstrated for texture discrimination using a support vector machine classi er in electrodes recording from primary and secondary somatosensory cortex [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The value of measured pinch distance was used to modulate the stimulation frequency, meanwhile pulse width and current amplitude were fixed as 200 µs and 3 mA, respectively. These two parameters have been used in our previous work [31,32]. Eight subjects in the previous study were recruited again in this study.…”
Section: Prosthetic Finger Position Controlmentioning
confidence: 99%